UPAYA MENGEMBANGKAN KEMAMPUAN MOTORIK HALUS ANAK MELALUI KEGIATAN MENGGUNTING KERTAS (POLA) - Panggabean, Ruth Donda Eleonora; Lumbantobing, Panni Ance; Farida, Niken (Unversitas Katolik Santo Thomas, 2022)
This study is a classroom action research aiming at developing fine motor skills of kindergarten students through paper-based paper cutting activities at TK Fajar Medan. The present study consisted of two cycles, in which each cycle included planning, acting, observing, and reflecting phases. This study was conducted collaboratively together with the homeroom teacher. A total of 8 students of Group A at TK Fajar Medan served as research subjects This research was conducted in October – Desembe 2021. Data collection instruments were observation, students’ performance, and documentation. The results showed that pattern- based cutting activities could develop Group A students’ fine motor skills at TK Fajar Medan in the academic year of 2020/2021. The data analysis results obtained the learning outcome percentage of students’ fine motor skills in pre-cycle was 24.75%, categorized as low. Then, in cycle I, the learning outcome percentage increased to 47.8%, and drastically increased in cycle II with a percentage of 81.37%. The study suggests that in order to develop fine motor skills, teachers can implement pattern-based cutting activities to students of Group A at TK Fajar Medan.